Analysis of Employee Placement on Employee Performance at the Regional Secretariat of the City of Pematangsiantar in 2024 - Nainggolan, Anju Bherna D.; Panjaitan, Hadi; Pardede, Nanda Rianty; Septianty , Diny Afrya; Sagala , Sara Mariani; Cahyani, Dewi Sri (ProBisnis : Jurnal Manajemen, 2024)
This study aims to analyze the relationship between employee placement and employee performance at the Regional Secretariat of Pematangsiantar City. This research uses a descriptive qualitative approach, with data collection conducted through documents and questionnaires distributed to employees. The results showed that employee placement has a significant relationship to their performance. Factors such as level of education, knowledge, skills and work experience play an important role in improving the quality of work, quantity of work and timeliness of employees in fulfilling their duties and responsibilities. However, the placement of employees at the Regional Secretariat of Pematangsiantar City is not fully optimal, because there are still employees who are placed not in accordance with their educational background or age that does not support the position. This study provides recommendations so that the employee placement process pays more attention to the right ones in order to increase the effectiveness of organizational performance.